PENGEMBANGA KOMIK EDUKASI ANTI BULLYING UNTUK SISWA KELAS V SD NEGERI 169 PEKANBARU - Jannah, Miftahul; Ramadan, Zaka Hadikusuma (PIONIR: JURNAL PENDIDIKAN, 2023)
Learning media are objects that exist in the surrounding environment, namely those that can be seen, heard and touched by the five senses that help in conveying messages that can be used in learning outside and in the classroom. This research method uses development research with a development model Formative Research. This study uses two stages. (1) preliminary, (2 level formative evaluation which covers levels self evaluation (analysis related to student needs, teacher needs and environmental analysis as well as the design and manufacture stages of anti educational comic media intimidation) and rate prototyping which includes stages member survey which is a test of validity and product revision. The subjects in this study were 2 teachers, 2 students and 6 expert validators consisting of 2 material experts, 2 language experts and 2 design experts. The instruments used were validation sheets and the data analysis techniques used were qualitative and quantitative. is. This research produces anti educational comic mediaintimidationwhich can be used for Selementary school as a medium that meets the very valid criteria, validation average score 1: material 88.45% language 63.63% and design 81.35%. validation average score 2: material 96.15%, language 93.14% and design 98.21%. Validation was carried out 2 times because it had obtained a very valid value with a feasibility percentage of 95.45% after the second validation was carried out. Through the percentage obtained, anti educational comicsintimidationThis is said to be valid and feasible to use.